2017
DOI: 10.5539/ijc.v9n4p87
|View full text |Cite
|
Sign up to set email alerts
|

Selective Synthesis of Ortho-Substituted 2-Aryl-3-phenyl-1,3-thiazolidin-4-one Sulfoxides and Sulfones by S-Oxidation with Oxone®

Abstract: S-oxidation of 2-aryl-3-phenyl-1,3-thiazolidin-4-ones with Oxone® was investigated. For all compounds evaluated, selective oxidation to the sulfoxide was realized using 3 equivalents of Oxone® at room temperature. Attempts to selectively prepare the sulfones of ortho-substituted 2-aryl-3-phenyl-1,3-thiazolidin-4-ones at high temperature by increasing the equivalents of Oxone® used were typically unsuccessful. These results contrast significantly with ortho-substituted 2-aryl-3-cyclohexyl-1,3-thiazolidin-4-ones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…from 1,3‐thiazolidin‐4‐ones 514 in the presence of oxone/MeOH (Scheme 159). [371] The reason for making these systems was because of the biological applicability for example against cancer cells in addition to their wide range of organic applications as well.Moreover, in another study, the same group has also reported a selective synthesis of ortho ‐substituted 2‐aryl‐3‐phenyl‐1,3‐thiazolidin‐4‐one sulfoxides 518 and sulfones 519 in 33–99 % yields from 2‐aryl‐3‐phenyl‐1,3‐thiazolidin‐4‐ones 517 viaS ‐oxidation by virtue of oxone‐mediated transformation as detailed in the Scheme 160 [372] …”
Section: Oxidation Of Diverse Functional Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…from 1,3‐thiazolidin‐4‐ones 514 in the presence of oxone/MeOH (Scheme 159). [371] The reason for making these systems was because of the biological applicability for example against cancer cells in addition to their wide range of organic applications as well.Moreover, in another study, the same group has also reported a selective synthesis of ortho ‐substituted 2‐aryl‐3‐phenyl‐1,3‐thiazolidin‐4‐one sulfoxides 518 and sulfones 519 in 33–99 % yields from 2‐aryl‐3‐phenyl‐1,3‐thiazolidin‐4‐ones 517 viaS ‐oxidation by virtue of oxone‐mediated transformation as detailed in the Scheme 160 [372] …”
Section: Oxidation Of Diverse Functional Groupsmentioning
confidence: 99%
“…[371] The reason for making these systems was because of the biological applicability for example against cancer cells in addition to their wide range of organic applications as well.Moreover, in another study, the same group has also reported a selective synthesis of orthosubstituted 2-aryl-3-phenyl-1,3-thiazolidin-4-one sulfoxides 518 and sulfones 519 in 33-99 % yields from 2-aryl-3-phenyl-1,3thiazolidin-4-ones 517viaS-oxidation by virtue of oxone-mediated transformation as detailed in the Scheme 160. [372] Generally, sulfoxides and sulfones are the vital class of compounds as they exhibit wide applications in organic synthesis, biology, agrochemicals, pharmaceuticals, and polymer chemistry. They also serve as valuable synthons in CÀ C bond formation, Diels-Alder reaction, as chiral auxiliaries, and in medicinal chemistry as antiulcer, cardiotonic agents, antihypertensive, CNS-stimulants besides vasodilators.…”
Section: Oxone-mediated Oxidation Reactions Of Diverse Organic Systemsmentioning
confidence: 99%